Frequency of chromosomal syndromes in the Brazilian population between 2017 and 2021 - Sarah Sousa Nascimento dos Santos; Adrhyann Jullyane de Sousa Portilho; Caroline Aquino Moreira-Nunes (Hospital de Clínicas de Itajubá, 2022)
Objective: To evaluate the frequency of chromosomal syndromes in the Brazilian population between 2017 and 2021. Methods: This is an active search of open access databases of the Information System on Live Births (SINASC) from the Brazilian Ministry of Health from 2017 to 2021. For statistical analysis, Analysis of Variance (One-way ANOVA) was followed by the Bonferroni post-test, considering a significant level of p < 0,05. The chi-square test was used for correlation analysis. Results: The underreporting of congenital anomalies in Brazil has decreased over the last few years, showing significant values; however, those numbers varied between regions. The chromosomal syndromes with the highest incidence were Down Syndrome (76.15%), Edwards and Patau Syndromes (14.59%) grouped in the same ICD-10, with the South and Southeast regions, with an average frequency of 0.07%, as the leader in notifications. The maternal variables with a higher incidence of chromosomal syndromes were women over 35 years of age, with 8 to 11 years of schooling, and married. Conclusion: There was a decrease in the value related to underreporting over the years. The data show a disparity in the notification of chromosomal syndromes between regions and outline the maternal profile of a higher incidence of chromosomal syndromes.